Clinical InvestigationsBiological effective dose evaluation and assessment of rectal and bladder complications for cervical cancer treated with radiotherapy and surgery - Beskow, Catharina; Ågren-Cronqvist, Anna-Karin; Lewensohn, Rolf; Toma-Dasu, Iuliana (Journal of Contemporary Brachytherapy, 2012)
Purpose: This study aims to retrospectively evaluate dosimetric parameters calculated as biological effective dose in relation to outcome in patients with cervical cancer treated with various treatment approaches, including radiotherapy with and without surgery. Material and methods: Calculations of biological effective dose (BED) were performed on data from a retrospective analysis of 171 patients with cervical carcinoma stages IB-IIB treated with curative intent, between January 1989 and December 1991. 43 patients were treated only with radiotherapy and 128 patients were treated with a combination of radiotherapy and surgery. External beam radiotherapy was delivered with 6-21 MV photons from linear accelerators. Brachytherapy was delivered either with a manual radium technique or with a remote afterloading technique. The treatment outcome was evaluated at 5 years. Results : The disease-specific survival rate was 87% for stage IB, 75% for stage IIA and 54% for stage IIB, while the overall survival rates were 84% for stage IB, 68% for stage IIA and 43% for stage IIB. Patients treated only with radiotherapy had a local control rate of 77% which was comparable to that for radiotherapy and surgery patients (78%). Late complications were recorded in 25 patients (15%). Among patients treated with radiotherapy and surgery, differences in radiation dose calculated as BED 10 did not seem to influence survival. For patients treated with radiotherapy only, a higher BED 10 was correlated to a higher overall survival (p = 0.0075). The dose response parameters found based on biological effective dose calculations were D 50 = 85.2 Gy10 and the normalized to total dose slope of the dose response curve γ = 1.62 for survival and D 50 = 61.6 Gy10 and γ = 0.92, respectively for local control. Conclusions : The outcome correlates with biological effective dose for patients treated with radiation therapy alone, but not for patients treated with radiotherapy and surgery. No correlations were found between BED and late toxicity from bladder and rectum.